Asesmen Diagnostik Sebagai Penilaian Pembelajaran Dalam Kurikulum Merdeka di MIN 2 Boyolali - Dwi Suprapti; Ahmad Rosyid Ridho (Lembag, 2024)
Diagnostic assessment is an assessment of learning assessment in the Merdeka Curriculum, which teachers conduct on students before the teacher designs learning. However, teachers' understanding of diagnostic assessment is still lacking, so it is challenging to compile diagnostic assessments. This study aims to describe diagnostic assessment as a learning assessment in the Merdeka Curriculum in elementary schools. The research method uses a literature study by collecting data from the results of exploring various literature in books and scientific articles from national and internationally reputable journals. The data analysis technique uses content analysis. The results obtained in this study indicate that there are two parts to the diagnostic assessment: the non-cognitive and cognitive diagnostic assessment. The non-cognitive diagnostic assessment aims to obtain information regarding family conditions, learning styles, characteristics, and students' learning interests. The cognitive diagnostic assessment aims to provide an overview of the initial abilities possessed by students in a subject topic. Teachers need to carry out diagnostic assessments of students to identify the abilities, strengths, and weaknesses so that teachers can design learning that is tailored to the abilities and characteristics of students.